Factors influencing ethical judgement of auditors in Malaysia / Hasnah Haron ... [et al.] - Haron, Hasnah; Ismail, Ishak; Ibrahim, Daing Nasir; Aw, Lo Na (Accounting Research Institute & Faculty of Accountancy, 2014)
Ethical issues involving Enron, Worldcom and Global Crossing have caused public confi dence on the auditing profession to decline. This study examines factors that influence the ethical judgement of auditors in Malaysia. These factors include gender, firm size, position level, perceived ethical climate of the firm and exposure to ethics. A total of 76 auditors responded to the questionnaires. Perceived ethical climate has a positive relationship with ethical judgement, whereas exposure to ethics has a negative relationship with ethical judgement. The Malaysian Institute of Accountants, the government and audit firms should consider introducing and maintaining a supportive ethical climate in audit firms and a clear policy on acceptable and unacceptable behaviours to improve the ethicality of auditors.